Unusual complication with an intramedullary lengthening device 15 months after implantation. Issue 10 (October 2015) - Tiefenböck, Thomas M.; Wozasek, Gerald E.
Abstract The treatment of leg length discrepancy and deformities has become more important over the last decades due to newly developed implants. Several different devices have been presented with various complications reported in literature. The purpose of this case report was to present an unusual complication 15 months after implantation of an intramedullary lengthening device (PRECICE®). An intramedullary lengthening device (PRECICE® P1 nail) was implanted in a 74 years old male patient with a congenital leg length discrepancy in January 2014. After bone lengthening of 6 cm and obvious radiological callus formation a nail breakage with severe deformity occurred 15 months after implantation. Physicians have to be aware of the risk of such late complications regarding this device with serious implications for the patient.